2019
DOI: 10.3390/su11061658
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Correlation of Formats in the Central Districts of a Megacity: The Case of Shanghai

Abstract: A “format” is an essential component of a city’s central districts and reflects their economic characteristics. In the urban context, individual formats relate to and mutually influence each other. Using data from two central districts in Shanghai—People’s Square and Lujiazui—and a case study approach, we investigated the mutual influences and relations among formats in these districts. We collected and categorized data on formats and assessed the degree of format aggregation. We also identified and described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Hu et al found that the distribution of formats in a downtown area was not balanced and identified and described three different types of spatial relationships that may exist between any two formats. Although the above studies investigate the layout and relationships of the formats in the format space, it does not explore the internal relationship between the formats and the rest of the business or the role of a single business within the space [16].…”
Section: Complementary and Collaborative Development Of Format Divisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al found that the distribution of formats in a downtown area was not balanced and identified and described three different types of spatial relationships that may exist between any two formats. Although the above studies investigate the layout and relationships of the formats in the format space, it does not explore the internal relationship between the formats and the rest of the business or the role of a single business within the space [16].…”
Section: Complementary and Collaborative Development Of Format Divisionmentioning
confidence: 99%
“…Hu [16] proposed that the degree of format aggregation represents the spatial correlation between the affected core area and the surrounding formats within a range of N meters and is expressed by the number of formats within this range. This suggests that formats, and other formats within the range of N meters, have strong spatial correlations.…”
Section: Degree Of Format Aggregationmentioning
confidence: 99%